Perceived accessibility: Literature review and future prospects - Ma, Xiaona; Cui, Fasheng (Journal of Transport and Land Use, 2024)
Perceived accessibility can fully present the cognitive status of different individuals and produce potential positive results. However, the literature on perceived accessibility is scattered across disciplines, which leads to problems of inconsistency in research paradigms and unclear mechanisms in perceived accessibility research. Moreover, the literature has not reached a consensus on the conceptual definition and measurement of perceived accessibility. Given this, the article first introduces the concept and measurement methods of perceived accessibility from four aspects: transportation modes, specific locations, particular things or activities, and activity participation opportunities. Next, it summarizes the antecedent variables of perceived accessibility from two perspectives, namely, objective factors and subjective factors, and the outcome variables from two perspectives, namely, behavioral factors and psychological factors. This reveals the practical impact of perceived accessibility on the cognition and behavior of urban managers. Finally, the study proposes four research directions with theoretical value and practical significance.